The effect of Adler's marital counseling module on conflict strategies, communication and stress among married couples - Othman, Mohd Hatta; Ku Johari, Ku Suhaila; Amat, Salleh; Yassin, Nurhafizah Mohamad (2025)
Marital conflict, poor communication and stress in marriage are among common issues faced by married couples which often leading to dissatisfaction and breakdowns in marriage. Effective interventions that specifically focus on these issues are essential for promoting a healthy and harmonious marriage. This study aims to test the effect of Adler's Marital Counseling Module on conflict strategies, communication and stress among married couples. A quasi-experimental research design is employed with pre-test, post-test, and follow-up test. The sample for this study consists of married couples who attend the Counselling Office, Majlis Agama Islam Negeri Sembilan (MAINS). 60 Participants were selected using purposive sampling with inclusion and exclusion criteria and were divided in two groups which are experiment group (n = 30) who received treatment of Adler's Marital Counseling Module and control group (n = 30) who received no treatment. Data was collected using the Romantic Partner Conflict Scale (RPCS), the Marital Communication Inventory (MCI), and the Perceived Stress Scale (PSS) during the assessment of pre-test, post-test and follow-up test. The analysis was conducted using both descriptive and inferential statistics which included the nonparametric Friedman Test. The results demonstrated that the experimental group experienced significant improvements in conflict strategies, particularly in the subscales of commitment, avoidance, interaction reactivity, and dominance. Follow-up tests confirmed the consistency of these improvements over time. Furthermore, Adler's Marital Counseling Module was effective in enhancing communication and maintaining consistency in communication variables, as well as reducing stress levels and ensuring the consistency of stress-related outcomes. The findings have practical implications for counsellors in designing counselling sessions that incorporate elements of conflict strategies, communication, and stress management for married couples. Future research should consider expanding the study sample to include participants from both urban and rural areas and exploring the role of spirituality in marital relationships